Balance Sheet Vulnerability and Macroeconomic Management in Indonesia - Goeltom, Miranda Swaray (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2005)
The economic and financial crises hitting Indonesia in 1997 have triggered a significant economic downturn. A critical issue addressed is how common shocks during crisis period have brought about macroeconomic outcome. The paper briefly discusses the problems, response and lessons learnt in the countryâs effort to restore the economy to its long-term potential growth path. By examining balance sheet conditions across sectors in the economy, it is shown that even though some progress has been achieved, overall balance sheet conditions are still vulnerable to further shocks that may hit the economy, so that efforts to restore economic growth and stability face substantial challenges. Considering these constraints, Indonesian macroeconomic policy makers focus their efforts on strengthening financial markets, among others, by developing bond markets and implementing banking architecture. However, various constraints will remain unless the government speeds up the necessary reforms, mostly institutional in nature.